Hydatid Cyst of the Adrenal Gland: Is Radical Surgery Necessary for Recurrent Hydatid Disease? - Sami Akbulut; Mehmet Yilmaz (Case Reports in Surgery)
Hydatid cyst disease caused by E. granulosus is a zoonotic disease that may involve many body tissues and organs, mainly liver. Adrenal glands are rarely involved even in regions where hydatid cyst disease is endemic. A limited number of studies have been reported on adrenal gland involvement by hydatid cyst disease. Herein, we aimed to report a recurrent case of adrenal hydatid cyst that was misdiagnosed as a hepatic hydatid cyst. A 16-year-old boy with a history of partial cyst excision and evacuation for perforated adrenal hydatid cyst disease three years ago presented to our outpatient clinic with nonspecific abdominal pain. Ultrasonography and computed tomography showed a lesion with an approximate size of 70 × 70 mm compatible with a hydatid cyst, which originated from the segment 5-6 of the liver and extended to the posterior-inferior direction. A surgical intervention was scheduled after a 2-week prophylactic albendazole treatment. During laparotomy using the old incision, it was noted that the cystic lesion that reportedly located in liver was actually a recurrent right adrenal cyst. As dense adhesions existed, the cystic lesion was excised en bloc with the right adrenal gland. As the lesion was totally removed without getting ruptured, albendazole was not administered at the postoperative period. No recurrence was observed at one-year follow-up.